SECURE ROAMING SERVICES FOR INTERNET OF THINGS ARCHITECTURE - kiruthika, D Vinu; Kavitha, J C (IJRDO -Journal of Computer Science Engineering, 2015)
Internet of things (IoT) is an emerging future networking paradigm. In IoT Communication betweenheterogeneous networks is very attractive. However ensuring secure roaming service among heterogeneousnetworks is challenging, since each network will have its own security policies that is different from one anotherit becomes difficult to fulfil the security requirements from heterogeneous networks and since the processingpower of most wireless devices could be limited, hence in such a resource constrained environment there is a needfor an encryption technique that should support the low processing speed and limited memory space. The proposedsystem focuses on providing a universal secure roaming architecture and multi-level privacy preservation.Security is achieved by encryption of data using elliptic curve cryptography which is lightweight, scalable andsecure. A conditional privacy-preserving authentication with access linkability aims to provide privacypreservation.